Richard Beilby interviewed by Hazel de Berg in the Hazel de Berg collection - Beilby, Richard, 1918-1989.; De Berg, Hazel, 1913-1984. (1976)
Beilby speaks of the beginnings of his writing career; his childhood in Malaysia; living in Perth; joining the Army and serving overseas during World War II. He describes the background to his first novel, "The sword and the myrtle"; his method of work and current work.
Also available online
Transcript available (12 p.)
Keywords: Beilby, Richard, -- 1918-1989 -- Interviews; Novelists, Australian -- Interviews